2003
DOI: 10.1095/biolreprod.103.015552
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ovarian Development in the FORKO Immature Mouse: Structural and Functional Implications for Ovarian Reserve

Abstract: Adult Follitropin Receptor Knockout (FORKO) female mice are infertile and estrogen deficient. In order to understand the peri/postnatal developmental changes, we have now characterized the structural and molecular aberrations by comparing several markers of follicular development in 2-, 10-, and 24-day-old wild-type and FORKO females. By Day 24, FORKO mice have 40%-50% smaller uteri and vaginas. Estradiol is undetectable but testosterone and LH levels are already elevated at this age. FORKO ovaries are 45% sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 68 publications
1
55
1
Order By: Relevance
“…However, luteinized granulosa cells have not been reported in the ovaries of FORKO mice, and this may reflect differences in the hormonal milieu when compared with SD hamsters. Plasma LH was elevated in FORKO mice relative to wild type and plasma estradiol was undetectable Balla et al (2003). Conversely, serum LH concentration has been reported to be much lower in SD than in LD female hamsters (Dodge & Badura 2002), but E 2 concentration does not appear to be consistently lower in SD when compared with LD hamsters (van den Hurk et al 2002, Scotti et al 2007; but see Moffatt-Blue et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, luteinized granulosa cells have not been reported in the ovaries of FORKO mice, and this may reflect differences in the hormonal milieu when compared with SD hamsters. Plasma LH was elevated in FORKO mice relative to wild type and plasma estradiol was undetectable Balla et al (2003). Conversely, serum LH concentration has been reported to be much lower in SD than in LD female hamsters (Dodge & Badura 2002), but E 2 concentration does not appear to be consistently lower in SD when compared with LD hamsters (van den Hurk et al 2002, Scotti et al 2007; but see Moffatt-Blue et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The uterus, a highly estrogen sensitive organ, weighs significantly less in female hamsters raised in SD when compared with LD (Ebling 1994 Scotti et al (2007) found no significant effect of photoperiod on serum E 2 concentration; however, their SD hamsters were adults that had been transferred from LD to SD, whereas van den Hurk et al (2002) transferred hamsters from LD to SD at birth. Because E 2 has been purported to both inhibit (Baarends et al 1995, Balla et al 2003 and stimulate (Ikeda et al 2002) ovarian AMH expression, it will be important to determine whether P450arom is expressed by luteinized granulosa cells and whether hamsters raised in SD in fact have higher serum E 2 concentrations than females reared in LD. Unfortunately, sample volume limitations precluded us from measuring serum E 2 in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, activin A is a negative regulator of preantral follicle growth, promoting these follicles to remain dormant and blocking follicle stimulating hormone (FSH)-induced granulosa cell proliferation (Mizunuma et al 1999). FSH is critical for the transition of follicles to the antral stage (Kumar et al 1997, Balla et al 2003, and for the follicle survival beyond the early antral stage (Hirshfield 1986, 1988. On the other hand, FAS/FASL and tumor necrosis factor a (TNFa) promote follicle atresia (Kaipia et al 1996, Hu et al 2001, Morrison & Marcinkiewicz 2002, Sasson et al 2002, Abdo et al 2003.…”
Section: Introductionmentioning
confidence: 99%